Factors Associated with Eye Strain Complaints Among Employees of Division Y PT X - Parulian Situmorang, Masyita Anggita Ayu; Muchamad Rifai (Universitas Ahmad Dahlan, 2025)
Background: Advances in information and communication technology have led to increased use of digital devices in various work sectors, particularly in office environments. Prolonged use of digital devices can cause eye strain or asthenopia. In Indonesia, the prevalence of blindness is recorded at 0,5%, and vision impairment ranks fifth among the most commonly reported occupational health complaints. This study aims to identify factors associated with eye strain complaints among employees in Division Y of PT X. Method: This study employs a quantitative approach using a cross-sectional study design. The study subjects were determined using total sampling, with 81 respondents. Respondent characteristics were collected using a questionnaire, lighting intensity scores were measured using a lux meter, and the Visual Fatigue Index (VFI) questionnaire was used to assess respondents' eye strain complaints. Data analysis was performed using univariate and bivariate analysis. Results: Statistical tests showed that age was associated with eye strain complaints with a p-value of 0,012. There was an association between gender and eye strain complaints with a p-value of 0,003. There was an association between computer/laptop screen time duration and eye strain complaints with a p-value of 0,010. The duration of screen time for smartphone use was associated with eye strain complaints, with a p-value of 0,047. Lighting intensity was associated with eye strain complaints, with a p-value of 0,000. However, job tenure was not associated with eye strain complaints, with a p-value of 0,513. Conclusion: Eye strain complaints in Division Y of PT X are associated with respondent characteristics (age and gender), as well as with screen time duration and lighting intensity. However, there is no association between work duration and eye strain complaints in Division Y of PT X.